Liver transplantation for acute liver failure due to antitubercular drugs – a single-center experience - Rodrigo Bronze de Martino; Edson Abdala; Felipe Castro Villegas; Luiz Augusto Carneiro D’Albuquerque; Alice Tung Wan Song (Clinics, 2018)
OBJECTIVES: Patients receiving treatment for tuberculosis are at risk of developing acute liver failure due to the hepatotoxicity of antitubercular drugs. We aimed to describe our experience with liver transplantation from deceased donors in this situation. METHODS: We identified patients undergoing transplantation for acute liver failure due to antitubercular drugs in our prospectively maintained database. RESULTS: Of 81 patients undergoing transplantation for acute liver failure, 8 cases were attributed to antitubercular drugs during the period of 2006-2016. Regarding the time of tuberculosis treatment until the onset of jaundice, patients were on antitubercular drugs for a mean of 64.7 days (21-155 days). The model for end-stage liver disease (MELD) score of patients ranged from 32 to 47 (median 38), and seven patients underwent transplantation under vasopressors. The 1-year survival was 50%. Three patients died during the week following transplantation due to septic shock (including a patient with acute liver failure due to hepatic/disseminated tuberculosis), and the remaining patient died 2 months after transplantation due to pulmonary infection. There were 2 cases of mild rejection and 1 case of moderate rejection. Of the surviving patients, all were considered cured of tuberculosis after alternative drugs were given. CONCLUSION: Patients arrived very sick and displayed poor survival after deceased donor transplantation.